Development Of Location Based Services For Geocoding And Recording Road Accidents Data - Al-Habshi, Mohammed Mustafa (2008)

(untitled)
This thesis explores and reviews both conceptual and technological issues associated with integrating mobile Geographic Information System (GIS) and Location Based Services (LBS); within the context of the study, road accident geocoding data collection as subject of the problem. The development approaches are discussed in this thesis from conceptual system modelling to integrating mobile-GIS and LBS middleware with the deployed map service, the developed geocoding service and data collections service. The developed system is partially based on open source software to reduce total cost of ownership for developing countries’ governments and to follow Malaysia government policy for year 2007 in adapting and developing open source solutions. The testing of the system and geocoding was carried out within the campus of Universiti Putra Malaysia. The conclusion of this research shows the LBS and mobile-GIS geocoding method have achieved improvement compared conventional method of geocoding and data collection; where each of positional errors and effort of data transferring have been reduced using these new technologies.